REVENGE PORN AND THE CHALLENGES OF VICTIM RECOVERY: A CASE STUDY OF REVENGE PORN VICTIMS IN INDONESIA - Ishaq, Fadhli Muhaimin; Adinda Rabiki Mardiah; Aini Syifa Mazida; Elisabeth Lue; Fayat Krisma Arsalan; Muhammad Rizky Al Fariz; Ragil Pangestika Reni (JIL : Journal of Indonesian Law, 2025)
This article analyzes legal protection and victim recovery challenges regarding revenge porn abuse involving male victims in same sex relationship in Indonesia. The research uses an empirical legal method with a case study approach through semi-structured interviews with the victim (initials E) who experienced threats of intimate video distribution for eight months. The study focuses on adequacy of the national legal framework, particularly the TPKS Law, ITE Law, and Pornography Law in dealing with image-based sexual abuse. The results of the study show that although there are provisions that can be used, there are no specific regulations governing revenge porn, resulting in ambiguity in law enforcement, a lack of victim centered recovery mechanisms, and a tendency to resolve cases through mediation. As a result, a number of victim rights, such as a sense of security, content removal, restitution, and rehabilitation, have not been fully fulfilled. This study emphasizes the urgency of strengthening legal norms, implementing trauma-based procedures, and explicitly recognizing revenge porn as an act of digital sexual violence.